Stability analysis of the pile-prestressed anchor composite structure based on failure mode. (July 2022) - Dong, Xuguang; LI, Zheng; Cui, Zizhi; Zhou, Canming
Abstract: Pile-prestressed anchor composite structure is widely used in retain engineering, whose stability analysis is mainly based on the slip line passing through the bottom of pile. However, the existing stability analysis is unable to comprehensively consider the actual slip line passing through pile body, pile bottom and the soil under pile. Based on multiple failure modes, a stability analysis model of composite structure considering both the effects of prestress and pile body is established, and the dynamic search algorithm for the model is proposed. We compare the proposed model with the software of LIZHENG deep foundation pit and the existing calculation model and find the effectiveness of our model. It is found that the safety coefficient of the composite structure is directly proportional to the prestress, pile length and pile diameter, but inversely proportional to the pile spacing. Meanwhile, the safety coefficient increases firstly and then decreases with the increase of slip line depth. Increasing the prestress of anchor in the middle and lower part of the slope has a more obvious effect on improving the safety coefficient. The proposed stability model and search algorithm can consider multiple failure modes and obtain the safety coefficient. In addition, it can comprehensively evaluate the stability of the pile-prestressed anchor composite structure retaining slope, which has superior application value.